Persistent and Recurrent Bacterial Bronchitis—A Paradigm Shift in Our Understanding of Chronic Respiratory Disease - Ishak, Alya; Everard, Mark L. (Frontiers in Pediatrics, 2017)
The recent recognition that the conducting airways are not ‘sterile’ and that they have their own dynamic microbiome, together with the rapid advances in our understanding of microbial biofilms and their roles in the causation of respiratory diseases (such as chronic bronchitis, sinusitis and chronic otitis media), permit us to update the ‘vicious circle’ hypothesis of the causation of bronchiectasis. This proposes that chronic inflammation driven by a persistent bacterial bronchitis, causes damage to both the epithelium, resulting in impaired mucociliary clearance, and to the airway wall, which eventually manifests as bronchiectasis. The link between a ‘chronic bronchitis’ and a persistence of bacterial pathogens such as non-typable Haemophilus influenza was first made more than a hundred years ago, and its probable role in the causation of bronchiectasis was proposed soon afterwards. The recognition that the ‘usual suspects’ are adept at forming biofilms and hence are able to persist and dominate the normal dynamically changing ‘healthy microbiome’ of the conducting airways, provides an explanation for the chronic colonisation of the bronchi and for the associated chronic neutrophil-dominated inflammation characteristic of a persistent bacterial bronchitis. Understanding the complex interaction between the host and the microbial communities of the conducting airways in health and disease will be a key component in optimising pulmonary health in the future.